Using Granulocyte Colonies Stimulant Factor in the Outpatient Treatment of Post Chemotherapy Neutropenia. Interesting Aspects for a General Comprenhensive Doctor. - Julio Dámaso Fernández Águila; Ana María Ramos Cedeño; Leslie Pérez Ruiz; Leobaldo Prieto Jiménez; Teresita Sabatés Llerandi (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2007)
-